Numerical Analysis of Hydrodynamic Resistance of a Joubert BB2-Type Submarine - Abiyyu Nafis Edfian (Walidem Institute and Publishing, 2026)
Objective: This study aims to analyze the hydrodynamic resistance characteristics of submarine hull designs suitable for Indonesia’s complex maritime environment, which includes shallow waters, strong currents, and deep-sea conditions. Minimizing resistance is essential to enhance operational efficiency, energy consumption, and maneuverability of submarines operating in such diverse waters. Theoretical framework: The theoretical framework of this research is grounded in naval hydrodynamics and resistance theory, particularly focusing on viscous and pressure resistance components acting on submerged bodies. The study also adopts the Theory of Change approach in naval design, emphasizing that optimized hull geometry leads to improved performance and operational effectiveness. Literature review: The literature review indicates that previous studies on submarine resistance have primarily focused on standard hull forms under idealized conditions, with limited attention to region-specific operational environments such as Indonesian waters. Comparative analyses of hull types such as teardrop, Joubert BB2, and ALFA class have been conducted, but systematic numerical evaluations under consistent submerged conditions remain limited. Methods: This research employs a quantitative numerical approach using Computational Fluid Dynamics (CFD). Simulations were conducted on three submarine hull types: teardrop hull, Joubert BB2, and ALFA class under submerged operating conditions at a constant speed of 10 knots. The CFD model analyzes total hydrodynamic resistance by resolving fluid flow behavior around each hull geometry, allowing for a detailed comparison of resistance performance. Results: The results reveal that the teardrop hull exhibits the lowest total resistance compared to the Joubert BB2 and ALFA class designs at the specified operational speed and submerged condition. This finding indicates superior hydrodynamic efficiency, reduced energy consumption, and enhanced maneuverability, making the teardrop hull particularly suitable for submarine operations in Indonesian waters. Implications: The implications of this study are both practical and strategic. Practically, the findings guide the selection of submarine hull designs that optimize operational efficiency and stability. Strategically, the results support future submarine development tailored to Indonesia’s maritime characteristics. Novelty: The novelty of this research lies in its comparative numerical analysis of multiple submarine hull types under a uniform submerged condition, specifically contextualized to Indonesian waters, offering design insights that bridge numerical simulation and operational needs. Future studies are recommended to validate these findings through experimental towing tank tests.